Forming Grinding Wheel Profile Modification of Cycloidal Gear of Robot RV Reducer - Deng Xiaozhong; Zhang Yanzhen; Li Tianxing; Su Jianxin (Jixie chuandong)
According to the principle of forming principle and modeling method of the cycloidal gear tooth profile,the mathematical model of the form grinding is established and the calculation formulas for axial section coordinate points of the grinding wheel are deduced. The profile equation of the grinding wheel is obtained through studying the theory of grinding wheel widened. The trajectory for the diamond wheel when dressing grinding wheelis solved based on the principle of equal distance curve. The software for form grinding wheel dressing is developed and the simulation and analysis of grind wheel modified is got by the modification method of "isometric + shift".